Glycosylation reduces the allergenicity of turbot (Scophthalmus maximus) parvalbumin by regulating digestibility, cellular mediators release and Th1/Th2 immunobalance. (15th July 2022) - Wu, Yeting; Lu, Youyou; Huang, Yuhao; Lin, Hong; Chen, Guanzhi; Chen, Yan; Li, Zhenxing
Graphical abstract: Highlights: Glycosylation treatments of turbot PV( T -PV) resulted in crosslinks formation. Glycosylation caused changes in the SGF and SIF digestion stability of T -PV. Glycated T -PV exhibited a weaker allergic reaction than native T -PV. Glycosylation to T -PV reduced the release of cellular mediators IL-4/IL-13. Glycosylation to T -PV decreased allergic responses by downregulating Th2 cytokines. Abstract: With turbot being increasingly consumed, turbot parvalbumin (TPV) allergy has become a pressing problem requiring immediate resolution. Glycosylation treatment not only resulted in cross-link formation but also caused changes in the simulated gastric fluid and simulated intestinal fluid digestion stability of TPV. In addition, KU812 experimentation revealed lower levels of β-hexosaminidase, histamine, tryptase, interleukin 4 (IL-4)/IL-13 in glycated protein-treated mice compared with native PV–treated ones. Glycated TPV exhibited a weaker allergic reaction compared with native TPV. Systemic anaphylaxis resulted in mild anaphylactic responses and reduced temperature, along with significantly increased levels of immunoglobulin E and histamine. Furthermore, glycosylation treatment reduced the release of cellular mediators and cytokines (IL-4/IL-13). Glycation to T -PV decreased allergic responses by downregulating Th2 cytokines, regulated the Th1/Th2 balance and effectively reduce the allergenicity and sensitisation ability of T -PV.